2017
DOI: 10.1177/1077558717744611
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmissions Reduction Program: Intended and Unintended Effects

Abstract: This study examines whether the Hospital Readmissions Reduction Program (HRRP), which penalizes hospitals with excess readmissions for certain conditions, has reduced hospital readmissions and led to unintended consequences. Our analyses of Florida hospital administrative data between 2008 and 2014 find that the HRRP resulted in a reduction in the likelihood of readmissions by 1% to 2% for traditional Medicare (TM) beneficiaries with heart failure, pneumonia, or chronic obstructive pulmonary disease. Readmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…Our analysis revealed hospitals that serve communities with minority and vulnerable populations, low socioeconomic status, low educational levels, high unemployment rates, and high percentage of Medicare recipients per 100,000 residents have increased readmissions. Current literature also indicates additional community and hospital characteristics (i.e., Medicare, Medicaid, education attainment) impact 30-day readmissions [9,11,12]. While the effect sizes are small (IRR close to 1), but significant [42] this research highlights how hospitals work in silos or as a part of their own health system and may not fully engage with the community.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our analysis revealed hospitals that serve communities with minority and vulnerable populations, low socioeconomic status, low educational levels, high unemployment rates, and high percentage of Medicare recipients per 100,000 residents have increased readmissions. Current literature also indicates additional community and hospital characteristics (i.e., Medicare, Medicaid, education attainment) impact 30-day readmissions [9,11,12]. While the effect sizes are small (IRR close to 1), but significant [42] this research highlights how hospitals work in silos or as a part of their own health system and may not fully engage with the community.…”
Section: Discussionmentioning
confidence: 78%
“…However, these calculations do not adjust for the diversity or socioeconomic status of the community in which a hospital resides. This lack of statistical control in the predictive model is problematic for hospitals that primarily serve diverse patients [12,13]. At the hospital level, previous research has consistently indicated hospitals serving minority populations experience higher readmissions for HF, AMI, PN, and diabetes [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Zuckerman et al (2016), Batt et al (2018b), and Wasfy et al (2017) report that the average readmission rates of Medicare patients have decreased after the introduction of HRRP. However Desai et al (2016), Chen and Grabowski (2019), and Wasfy et al (2017) (among others) show that hospitals with the highest pre-HRRP readmission levels had the greatest improvement. In addition, Mellor et al (2017) and Ziedan (2018) demonstrate (using different identification strategies) that there is a statistically significant decrease in readmission rates only for AMI patients for low-performing hospitals.…”
Section: First Letmentioning
confidence: 97%
“…In addition, outcome and readmission data have been made publically available to guide decision-making and improvements in care. [8][9][10] After the initial success of the program for medical conditions (e.g. myocardial infarction, pneumonia, heart failure), HRRP has continued to expand with the recent inclusion of major surgical procedures.…”
Section: Introductionmentioning
confidence: 99%